Randomized, controlled, parallel‐group trial of routine prophylaxis vs. on‐demand treatment with sucrose‐formulated recombinant factor VIII in adults with severe hemophilia A (SPINART). Issue 6 (3rd July 2013) - Manco‐Johnson, M. J.; Kempton, C. L.; Reding, M. T.; Lissitchkov, T.; Goranov, S.; Gercheva, L.; Rusen, L.; Ghinea, M.; Uscatescu, V.; Rescia, V.; Hong, W.
Summary Background The benefits of routine prophylaxis vs. on‐demand treatment with factor VIII products have not been evaluated in controlled clinical trials in older patients with hemophilia A. Objectives To report results from a preplanned analysis of data from the first year of the 3‐year SPINART study, which compares routine prophylaxis with on‐demand treatment with sucrose‐formulated recombinant FVIII (rFVIII‐FS). Patients/Methods SPINART is an open‐label, randomized, controlled, parallel‐group, multinational trial. Males aged 12–50 years with severe hemophilia A, ≥ 150 days of exposure to FVIII, no FVIII inhibitors, no prophylaxis for > 12 consecutive months in the past 5 years and 6–24 bleeding episodes in the preceding 6 months were randomized 1 : 1 to rFVIII‐FS prophylaxis (25 IU kg−1, three times weekly) or on‐demand treatment. The primary efficacy endpoint, number of total bleeding episodes in the intent‐to‐treat population, was analyzed after the last patient had completed 1 year of follow‐up. A negative binomial model was used for the primary endpoint analysis; analysis of variance was used for confirmatory analysis of annualized bleeding rates. Results Eighty‐four patients were enrolled and analyzed (n = 42 per group; mean age, 30.6 years; median treatment duration, 1.7 years). The median number of total bleeding episodes and total bleeding episodes per year were significantly lower with prophylaxis than with on‐demand treatment (total, 0 vs. 54.5; total per year, 0 vs. 27.9; both P < 0.0001). No treatment‐related adverse events occurred, and no patients developed FVIII inhibitors. Conclusions Routine prophylaxis with rFVIII‐FS leads to a significant reduction in bleeding as compared with on‐demand treatment. Adverse events were consistent with the established rFVIII‐FS safety profile.